(3GdeMGSHI GdeGdjI (B:s (3Hjf GdfXQjI h GdJWHjb (B/s - (3cMGdI, LHQGFjds; (3GdNWjH, NGdO s; (3Zfje, QeVGf eMeO s ((3YeGf(B: s (3OGQ RgQGf(B, s, 1997)
(3WHjYI GdeMGSHI GdeGdjI h eLGdgG , GdeaGgje h GdaQhV h GdeHGOF GdeMGSHjI , WQb GdbjO GdeMGSHj , GdebheGJ GdCSGSjI ddfXGe GdeMGSHj , GdJSLjd h GdJHhH GdeMGSHj , eYGdLI GdYedjGJ GdJehjdHI h GdQCSeGdjI , eYGdLI GdYedjGJ GdfbOjI , eYGdLI GdYedjGJ GdHfcjI , eYGdLI YedjGJ GdTQGA h GdHjY , eYGdLI GdGhQGb GdJLGQjI , ejRGf GdeQGLYI h JUMjM GdGNWGA , GdMSGHGJ GdNJGejI h bGFeI GdONd , GdejRGfjI (B( (3bGFeI GdeQcR GdeGdj (B).s
(3eQGLY U(B.377s
Keywords: (3GdeGdjIs; (3GdeMGSHIs